Transformation of Poland's Spatial-Economic Structure in the Years 1998-2008 - Czyż, Teresa (Quaestiones Geographicae, 2012)
The article consists of two parts. Part one offers a diagnostic description of the current spatial-economic structure of Poland in which regions are divided into core and peripheral ones. The division rests on a systemic measure of the level of economic development, viz. the income potential / population potential ratio. Part two is an analysis of changes in Poland's spatial-economic structure over the years 1998-2008 where an attempt is made to determine how far those changes coincided with visions of the country's spatial structure presented in planning conceptions.